The customs union between Belarus, Kazakhsthan and Russia: An overwiew of economic implications for Belarus - Irina Tochitskaya (Center for Social and Economic Research (CASE), 2010)
The paper examines the economic implications of Belarus' participation in the newly created EURASEC Customs Union. The results of the calculations show that after the introduction of a common external tariff (CET) the level of tariff protection in Belarus has not increased noticeably. The reduction in the volume of imports from non-CIS countries equal to USD 1.1 bn (8% of Belarusian non-CIS import in 2008) will be mainly brought about by cancellation of used cars imports from non-member countries. The analyses revealed that Belarusian budget can benefit from participation in the Customs Union (CU). The amount of possible gain will be about 28.3% of total budget revenues from customs duties and customs charges in 2008 due to the fact that approximately 40% of Russian imports may go through customs clearance in Belarus owning to less bureaucracy at the border with respect to Russia, and the revenues from customs charges, which is not planned to be distributed among member countries, will be transferred to Belarusian budget. However, it is unlikely that CU membership will increase foreign direct investment (FDI) inflow to Belarus, since in the case of South-South regional trade agreements (the type of EURASEC countries CU) FDI usually goes to the bigger country, i.e. to the bigger market. Therefore, most probably that in the regional arrangement in question Russia followed by Kazakhstan will be the main beneficiaries of foreign direct investments.
Keywords: F13; F15; 330; Customs Union; import; MFN Tariff; Wirtschaftsintegration; Zollunion; Mitgliedschaft; Meistbegünstigung; Weißrussland; Kasachstan; Russland